Perspectives and Emotional Experiences of Patients With Chronic Myeloid Leukemia During ENESTPath Clinical Trial and Treatment-Free Remission: Rationale and Protocol of the Italian Substudy - Borghi, Lidia; Rosti, Gianantonio; Maggi, Alessandro; Breccia, Massimo; Di Bona, Eros; Iurlo, Alessandra; La Barba, Gaetano; Sportoletti, Paolo; Albano, Francesco; Galimberti, Sara; Rivellini, Flavia; Cambrin, Giovanna Rege; et al. (Frontiers in Oncology, 2021)
Achievement of deep molecular response following treatment with a tyrosine kinase inhibitor (TKI) allows for treatment-free remission (TFR) in many patients with chronic myeloid leukemia (CML). Successful TFR is defined as the achievement of a sustained molecular response after cessation of ongoing TKI therapy. The phase 3 ENESTPath study was designed to determine the required optimal duration of consolidation treatment with the second-generation TKI, nilotinib 300 mg twice-daily, to remain in successful TFR without relapse after entering TFR for 12 months. The purpose of this Italian ‘patient’s voice CML’ substudy was to evaluate patients’ psycho-emotional characteristics and quality of life through their experiences of stopping treatment with nilotinib and entering TFR. The purpose of the present contribution is to early present the study protocol of an ongoing study to the scientific community, in order to describe the study rationale and to extensively present the study methodology. Patients aged ≥18 years with a confirmed diagnosis of Philadelphia chromosome positive BCR-ABL1+ CML in chronic phase and treated with front-line imatinib for a minimum of 24 months from the enrollment were eligible. Patients consenting to participate the substudy will have quality of life questionnaires and in-depth qualitative interviews conducted. The substudy will include both qualitative and quantitative design aspects to evaluate the psychological outcomes as assessed via patients’ emotional experience during and after stopping nilotinib therapy. Randomization is hypothesized to be a timepoint of higher psychological alert or distress when compared to consolidation and additionally any improvement in health-related quality of life (HRQoL) due to nilotinib treatment is expected across the timepoints (from consolidation, to randomization, and TFR). An association is also expected between dysfunctional coping strategies, such as detachments and certain personality traits, and psychological distress and HRQoL impairments. Better HRQoL outcomes are expected in TFR compared to the end of consolidation. This substudy is designed for in-depth assessment of all potential psycho-emotional variables and aims to determine the need for personalized patient care and counselling, and also guide clinicians to consider the psychological well-being of patients who are considering treatment termination.